Dectin-1 Facilitates IL-18 Production for the Generation of Protective Antibodies Against Candida albicans - Shen, Hui; Yu, Yuetian; Chen, Si-Min; Sun, Juan-Juan; Fang, Wei; Guo, Shi-Yu; Hou, Wei-Tong; Qiu, Xi-Ran; Zhang, Yu; Chen, Yuan-Li; Wang, Yi-Da; Hu, Xin-Yu; et al. (Frontiers in Microbiology, 2020)
Invasive candidiasis (IC) is one of the leading causes of death among immunocompromised patients. Because of limited effective therapy treatment options, prevention of IC through vaccine is an appealing strategy. However, how to induce the generation of direct candidacidal antibodies in host remains unclear. Gpi7 mutant C. albicans is an avirulent strain that exposes cell wall β-(1,3)-glucans. Here, we found that vaccination with the gpi7 mutant strain could protect mice against invasive candidiasis caused by C. albicans and non-albicans Candida spp. The protective effects induced by gpi7 mutant relied on long-lived plasma cells (LLPCs) secreting protective antibodies against C. albicans. Clinically, we verified a similar profile of IgG antibodies in the serum samples from patients recovering from IC to those from gpi7 mutant-vaccinated mice. Mechanistically, we found cell wall β-(1,3)-glucan of gpi7 mutant facilitated Dectin-1 receptor dependent nuclear translocation of noncanonical NF-κB subunit RelB in macrophages and subsequent IL-18 secretion, which primed protective antibodies generation in vivo. Together, our study demonstrate that Dectin-1 engagement could trigger RelB activation to prime IL-18 expression and established a new paradigm for consideration of the link between Dectin-1 mediated innate immune response and adaptive humoral immunity, suggesting a previously unknown active vaccination strategy against Candida spp. infection.